Pengaruh Pendapatan Masyarakat,Tingkat Pendidikan, dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Membayar Pajak Bumi dan Bangunan Di Desa Gebugan, Kecamatan Bergas, Kabupaten Semarang - Widya Vinda Indriyasari; Maryono Maryono (Owner : Riset dan Jurnal Akuntansi, 2022)
Land and Building Tax is a levy on land and buildings that arises because of the advantages and/or socio-economic position of a person or entity who has a right to it, or obtains benefits from it. Land and Building Tax is one of the factors of income for the state which is quite potential for state income. The strategic land and building tax is none other than because the object of the tax covers all land and buildings within the territory of the Unitary State of the Republic of Indonesia. Land and Building Tax is considered a potential source of funds for state financing. The purpose of this study was to determine the effect of people's income, education level, and knowledge of taxation on taxpayer compliance in paying land and building taxes. The population in this study were taxpayers in Gebugan Village, Bergas District, Semarang Regency, which amounted to 3,540 people. Sampling amounted to 100 taxpayers using the slovin formula. This research data is primary data which is carried out through distributing questionnaires to respondents. The data analysis technique used multiple linear regression. The results of this study indicate that income level has a positive effect on land and building taxpayer compliance, education level has no effect on land and building taxpayer compliance, and tax knowledge has a positive effect on land and building taxpayer compliance.